2020
DOI: 10.1007/s10311-020-00975-1
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in soils from antimony mining sites: geochemical control promotes species enrichment

Abstract: Elevated soil concentrations of antimony (Sb) and co-contaminants are frequently encountered where antimony has been mined on a large scale. For instance, the Xikuangshan antimony mine in central South China has sustained, over many centuries, dispersed and spatially variable input of toxic elements into the soil ecosystem. We utilized this unique environment to assess the impact of geochemical conditions on soil microbiology. Geochemical conditions were assessed by monitoring absolute and available fractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 50 publications
(104 reference statements)
3
13
0
Order By: Relevance
“…In comparisons of the relative abundance of microbial communities and α-diversity in the three mine waste types, the microbial diversity in waste rock with relatively low Sb and As content was higher than that of the other two waste types, and it was hypothesized that the two metalloids had an inhibitory effect on the development of microbial communities. The main microorganisms in the mine waste were Proteobacteria , Bacteroidota , Acidobacteriota , and Actinobacteriota , which is consistent with previous studies [ 34 , 56 , 57 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 92%
“…In comparisons of the relative abundance of microbial communities and α-diversity in the three mine waste types, the microbial diversity in waste rock with relatively low Sb and As content was higher than that of the other two waste types, and it was hypothesized that the two metalloids had an inhibitory effect on the development of microbial communities. The main microorganisms in the mine waste were Proteobacteria , Bacteroidota , Acidobacteriota , and Actinobacteriota , which is consistent with previous studies [ 34 , 56 , 57 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the relative abundance of Acidobacteriia was significantly higher in metal-rich soils than those with lower metal content. Enrichment of Acidobacteriia in the metalrich sites, such as As and Cr (Sheik et al, 2012), Hg (Xu et al, 2019), Sb (Deng et al, 2020) and Au (Sanyal et al, 2019), was observed in previous studies. Therefore, metal(loid) content may be an important factor influencing the abundances of Acidobacteriia in addition to pH.…”
Section: Discussionsupporting
confidence: 64%
“…Overall, Spartobacteria correlated negatively with compounds from cluster C (Fig. S2) and have recently been found sensitive to toxic elements in antimony mining sites (Deng et al ., 2020). This could explain the negative correlation and complete absence of some of the OTUs in the contaminated locations.…”
Section: Discussionmentioning
confidence: 99%